CERAMBICIDOS XILOFAGOS DEENCINAS Y ALCORNOQUES: ESTUDIO BIOECOLOGICO Y CONTROL DEPOBLACIONES (Bol. Inf. CIDEU, 2006)
The aim of this work is to present recent advances on the knowledge of holm oak and cork oak woodborers (Coleoptera: Cerambycidae) in Huelva (Andalussia, Spain). Cerambyx welensii and Prinobius germari are considered the main implicated species. We emphasize over the differences of behavior founded among them: the first species is little territorial and very movable, Prinobius seems to show a more territorial and sedentary behavior, specially the males. After the analysis of diverse options for population control of insects with similar habits, a strategy of Integrated Management is recommended, having as one of his pillars the attraction of these species for his capture and/or the specific repelence or confusion; that is to say, the applied study of semiochemicals compounds to integrated pest management.